Alames turns 24 - Edmundo Humberto Granda Ugalde (Social Medicine Publication Group, 2008)
Juan Cesar García pointed out four fundamental characteristics of social medicine, as it was developed in Europe during the 19th Century. These four characteristics can guide our actions in the American Continent of today: a) political commitment to change, b) health/illness as a social fact, c) the importance of science in the construction of the discipline and d) the responsibility of the State for health. In this paper I have tried to illustrate certain issues: 1) the historical roots and meaning of the term social medicine and b) the delineation of its particular characteristics. I have also examined three simultaneous evolutions: c) from a focus on health/illness to an emphasis on health practice, d) from the insistence on establishing differences between disciplines to the search for unity in action, and e) from the academic arena to other fields of practice. We have been creating our identity through social medicine as a transformative political program that fights for the right to health, built with the support of different viewpoints and via consensual methods. The potential for our further development lies in the expansion of transformative experiences in the field of collective health that enable the opening spaces and paths toward the fight for health as a right through the commitment and empowerment of the people.